1991
DOI: 10.2134/jpa1991.0481
|View full text |Cite
|
Sign up to set email alerts
|

Cool-Season Annuals for Supplementing Perennial Pasture on Beef Cow-Calf Productivity

Abstract: The cow‐calf operation is the primary beef cattle enterprise in the Southeastern USA. Cool‐season annuals can be used to improve forage production and quality with the long growing season that the Gulf Coast offers. The objective of this study was to determine the effect of supplemental grazing of cool‐season annuals, sodseeded on perennial Argentine bahiagrass (Paspalum notatum Flugge) pasture, had on cow‐calf productivity. Five hundred forty‐seven reproductive and calving records obtained over 8 yr from ISO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 6 publications
0
17
1
Order By: Relevance
“…The hot and dry periods during the summer prevent or impede persistence of cool‐season perennial grasses in the lower southeastern U.S. Cool‐season annuals such as small grains, annual ryegrass, and legumes are frequently overseeded into warm‐season perennial grass pastures in autumn to move closer to a year‐round growing season. The cool‐season forages provide winter and spring grazing that reduce the need for stored forages (2); have a higher nutritive value that results in better animal performance than warm‐season grasses (3); provide spring weed control (4); and, if a legume, adds nitrogen to the pasture system (5). The overseeding of warm‐season perennial grasses avoids erosion since there is no deep tillage.…”
Section: Introductionmentioning
confidence: 99%
“…The hot and dry periods during the summer prevent or impede persistence of cool‐season perennial grasses in the lower southeastern U.S. Cool‐season annuals such as small grains, annual ryegrass, and legumes are frequently overseeded into warm‐season perennial grass pastures in autumn to move closer to a year‐round growing season. The cool‐season forages provide winter and spring grazing that reduce the need for stored forages (2); have a higher nutritive value that results in better animal performance than warm‐season grasses (3); provide spring weed control (4); and, if a legume, adds nitrogen to the pasture system (5). The overseeding of warm‐season perennial grasses avoids erosion since there is no deep tillage.…”
Section: Introductionmentioning
confidence: 99%
“…ers in the southern United States still winter cows primarily with hay plus a concentrate-based, high-CP supplement. Complementary forage systems based on warm-season perennial grasses and cool-season annual grasses have shown promise as a method of providing supplemental nutrients and decreasing hay requirements (Utley and McCormick, 1978;Hill et al, 1985;DeRouen et al, 1991). The common advantages noted in these reports are extension of the grazing season and decreased days and quantities of hay feeding required.…”
Section: Introductionmentioning
confidence: 99%
“…extended the number of available grazing days/ha from 178 to 240. Studies in northern Florida that evaluated the use of wheat (Triticum aestivum L.) or rye (Secale cereale L.) with crimson (Trifo-lium incarnatum L.) and arrowleaf (Trifolium vesiculosum Savi) clover as a supplement to Argentine bahiagrass (Paspalum notatum Flugge) hay (DeRouen et al, 1991) demonstrated that winter-annual pasture grazing could decrease winter hay DMI by as much as 30% compared to bahiagrass hay plus a concentratebased protein supplement.…”
Section: Introductionmentioning
confidence: 99%
“…Coats (1957) found that crops drilled into permanent pastures offer an excellent opportunity for extending the grazing season and for producing hay or grain from pastureland that would otherwise be left idle during the winter months. Overseeding warm-season perennial grasses with cool-season annuals is a common practice in the southeastern United States to extend the grazing season and thereby reduce the winter feeding period, which is the greatest expense for maintaining beef cattle throughout the year (DeRouen, Prichard, Baker, Jr., & Stanley, Jr., 1991;Mooso, Feazel, & Morrison, 1990). Grazing these sod-seeded forages offers the potential to improve land use efficiency (Moyer, Coffey, Brazle, & Schneider, 1995) and to improve animal gains relative to gains expected from cattle grazing other dormant forages during the winter (Ellis & Lippke, 1976;Wilkinson & Stuedemann, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Grazing these sod-seeded forages offers the potential to improve land use efficiency (Moyer, Coffey, Brazle, & Schneider, 1995) and to improve animal gains relative to gains expected from cattle grazing other dormant forages during the winter (Ellis & Lippke, 1976;Wilkinson & Stuedemann, 1983). The cool-season forages provide winter and spring grazing that reduce the need for stored forages (DeRouen, Prichard, Baker, Jr., & Stanley, Jr., 1991); have a greater nutritive value that results in better animal performance than warm-season grasses (Ellis & Lippke, 1976); provide spring weed control (Evers, 1983); and, if a legume, adds nitrogen to the pasture system (Evers, 1985). Seasonal forage production from winter annual forages varies considerably across forages and climatic conditions, and interseeding these forages into sods of warm season perennial grasses generally increases this variability (Moyer & Coffey, 2000).…”
Section: Introductionmentioning
confidence: 99%